Facilitated electron transfer by Mn dopants in 1-dimensional CdS nanorods for enhanced photocatalytic hydrogen generation. Issue 13 (14th March 2023) - MacSwain, Walker; Lin, Hanjie; Li, Zhi-Jun; Li, Shuya; Chu, Chun; Dube, Lacie; Chen, Ou; Leem, Gyu; Zheng, Weiwei
Abstract : The long lifetime of Mn 2+ dopants (∼ms) facilitates charge separation and electron transfer in Mn 2+ doped 1D CdS nanorods (NRs) with Pt tips ( i.e., Mn:CdS-Pt NRs), which significantly enhances photocatalytic water splitting for hydrogen generation. Abstract : Using sunlight to produce hydrogen gas via photocatalytic water splitting is highly desirable for green energy harvesting and sustainability. In this work, Mn 2+ doped 1-dimensional (1D) CdS nanorods (NRs) with Pt tips ( i.e., 1D Mn:CdS-Pt NRs) were synthesized for photocatalytic water splitting to generate hydrogen gas. The incorporation of Mn 2+ dopants inside the 1D CdS NRs with a significantly longer lifetime (∼ms) than that of host excitons (∼ns) facilitates charge separation; the electron transfer to metal Pt tips leads to enhanced photocatalytic activity in water splitting redox reactions. The as-synthesized Mn 2+ doped CdS NR-based photocatalyst generated an order of magnitude greater yield of hydrogen gas compared to the undoped CdS NR-based photocatalyst. The enhanced charge transport from the long lifetime excited state of Mn 2+ dopants in light harvesting semiconductor nanomaterials presents a new opportunity to increase the overall photocatalytic performance.